Strengthening Cultural Heritage Values Through Nonformal Education Using Zapin Pecah Dua Belas in Riau - Nike Suryani; M. Jazuli; Agus Cahyono; M. Ibnan Syarif (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
This study aims to investigate the role of non-formal education in strengthening cultural heritage through learning the zapin Pecah Dua Belas dance in the local community. The Zapin Pecah Dua Belas dance is an integral part of the traditional culture of the local community, but faces challenges in preserving it. This research method uses a qualitative approach. Data were collected through participatory observation, in-depth interviews with instructors and participants, and analysis of related documents. The results of the study show that non-formal education has an important role in strengthening cultural heritage through learning the zapin Pecah Dua Belas dance. This learning teaches dance movements and techniques, and provides a deeper understanding of the meanings and cultural values contained in dance. The novelty of this study lies in the non-formal educational approach adopted, that is, an approach that not only focuses on the technical aspects of dance, but also on a deep understanding of the cultural meaning behind zapin Pecah Dua Belas dance. Non-formal education plays an important role in preserving cultural heritage through the teaching of zapin Pecah Dua Belas dance. This training not only teaches dance movements, but also develops a deep understanding of cultural values and people's identities.